Contribution of COMT and BDNF Genotype and Expression to the Risk of Transition From Acute to Chronic Low Back Pain. Issue 6 (June 2020) - Baumbauer, Kyle M.; Ramesh, Divya; Perry, Mallory; Carney, Katherine B.; Julian, Thomas; Glidden, Nicole; Dorsey, Susan G.; Starkweather, Angela R.; Young, Erin E.
Abstract : Objectives: A number of factors, including heritability and the environment, contribute to risk of transition from acute low back pain to chronic low back pain (CLBP). The aim of this study was to (1) compare somatosensory function and pain ratings at low back pain (LBP) onset between the acute low back pain and CLBP conditions and (2) evaluate associations between BDNF and COMT polymorphisms and expression levels at LBP onset to acute and chronic pain burden and risk for transition to the chronic pain state. Methods: In this longitudinal study, 220 participants were enrolled following recent onset of LBP and data were collected until the LBP resolved or until the end of the study at 6 months. Forty-two participants' pain resolved before 6 weeks from onset and 42 participants continued to have pain at 6 months. Patient-reported pain burden, somatosensory function (quantitative sensory testing), and blood samples were collected at each study visit. Results: CLBP is associated with greater pain burden and somatosensory hypersensitivity at the time of LBP onset. COMT rs4680 genotype (GG) was associated with acute cold pain sensitivity and with the risk for transition to CLBP while COMT expression was independently associated with risk for transition. Discussion: CLBP was characterized by higher reported pain burden and augmented hypersensitivity at LBP onset. COMT expression and genotype were associated with acute pain burden and likelihood of transition to CLBP.